Adaptive bit and subcarrier allocation algorithm for multiuser OFDM/OQAM systems. (1st January 2011) - Baamrani, Khalid El; Habib, Ayad; Elassali, Raja
OFDM/OQAM technique is one of the leading candidates for future wireless systems. This technique does not employ guard regions and as a direct consequence, the wasted resources (time/power) allocated to the guard interval in the OFDM/QAM system are directly used to convey useful data; this guarantees a higher spectral efficiency and a throughput increase. The objective of this paper is to maximise the sum of the users data rates subject to the overall transmit power constraint and BER requirement for multiuser OFDM/OQAM downlink transmission. As demonstrated in the simulation results, the proposed OFDM/OQAM algorithm offers better performance than previous OFDM/QAM algorithms in the literature.